Analisis Pertimbangan Hakim Terhadap Hinaan Masyarakat Sebagai Alasan Meringankan Hukum Pidana Dalam Perspektif Keadilan (Studi Putusan Nomor 29/Pid.Sus-Tpk/2021/Pn.Jkt.Pst) - Hawanda Paonganan, Lucky; Insan Tajali Nur; Khristyawan Wisnu Wardana (Jurnal Ilmu Hukum, 2024)
This research aims to analyze the judge's consideration of public insults as a reason to reduce criminal sentences in cases of criminal acts of corruption based on Decision Number: 29/Pid.Sus-Tpk/2021/PN.Jkt.Pst. The research method used is normative juridical research with a case study approach. Primary data was obtained through court decision documents, while secondary data was collected from relevant legal literature, journals and other legal sources. The results of the research show that in the judge's consideration, public insults are often used as one of the reasons for mitigating criminal sentences. This is based on the view that social pressure and negative stigma from society can have a significant psychological effect on the defendant, which in some cases can be considered a form of additional punishment beyond the sentence imposed by the court. In the decision studied, the judge considered that the defendant had experienced severe social pressure due to insults and ridicule from society, which was then used as a reason to reduce the criminal sentence imposed. This research also found that the use of public insults as a reason to reduce criminal sentences still raises pros and cons among legal practitioners and academics. Some parties argue that this reason should not be used because it can reduce the deterrent effect of criminal punishment. On the other hand, other parties argue that these considerations need to be taken into account to provide more humane justice for the defendant. The conclusion of this research is that the judge's consideration of public insults as a reason to reduce criminal sentences has a strong basis in an effort to achieve a balance between legal justice and social justice. However, there needs to be clearer and more consistent guidelines in the application of these reasons to ensure objective and equitable justice.